Population isolation predicts the severity of historical human epidemics. Issue 6 (3rd April 2018) - Start, Denon; Kirk, Devin
Abstract: Aim: Infectious diseases are a major source of human mortality and have altered human history. Despite their importance, we lack a thorough understanding of why some historical epidemics were more deadly than others. For many organisms, geographically isolated populations (e.g., populations distant from the mainland) experience more severe epidemics, including after long periods of isolation. These patterns are likely to arise because geographical isolation reduces contact with infectious diseases, causing a corresponding naïvety and susceptibility to those pathogens. Here, we test for equivalent patterns in human populations, but over much longer time frames than have been considered previously. Location: Global, but with a particular focus on islands in the Americas and the Pacific. Time period: Approximately 1000–1920 CE. Major taxa studied: Humans and two of their pathogens: smallpox and influenza. Methods: We used historical mortality data from populations afflicted with smallpox or Spanish flu to test for relationships between isolation, a suite of covariates (e.g., island size, population density) and epidemic severity (mortality rate). Results: We show that populations isolated from the mainland suffered greater mortality. Interestingly, New World populations suffered universally higher mortality during smallpox epidemics, probably because they became isolated before the appearance of smallpox, causing high levels of susceptibility. Conversely, by 1918 New World populations were predominantly Eurasian and thus historically exposed to influenza, causing low mortality. Conclusion: Human populations exhibit patterns of epidemics analogous to those in non‐human species; isolated populations tend to suffer more severe epidemics. However, historical contingencies can cause patterns to diverge from those typically observed among other free‐living species. Generally, we suggest that geography underlies the ecology and evolution of humans and their pathogens.